Spotlight on people and print: Old Town Albuquerque. - Hertzog, Peter (1964)
A thin little book by Peter Hertzog called Old Town Albuquerque gives us a lively account of the history of the "Duke City".
3 pg typed story about Old town Albuquerque.
Master list item # 9
File location is in the New Mexico Cities and Towns
Keywords: Albuquerque, New Mexico; Hertzog, Peter -- Author -- Albuquerque, New Mexico